The complete chloroplast genome of Actinidia fulvicoma - Zhang, Fuquan (Mitochondrial DNA B Resour, 2019)
The species of genus Actinidia are economically and nutritionally important fruits with remarkably high vitamin C content. Here, we assembled and characterized the complete chloroplast (cp) genome sequence of Actinidia fulvicoma (A. fulvicoma) using Illumina paired-end sequencing data. The cp genome is 157,339 bp in length, including a large single-copy region (LSC) of 88,741 bp, a small single-copy region (SSC) of 20,512 bp, and a pair of 24,043 bp inverted repeat (IR) regions. A total of 131 genes, consisting of 85 protein-coding genes, 38 tRNA genes, and 8 rRNA genes, were annotated in the A. fulvicoma cp genome. Phylogenetic analysis confirmed the evolutionary position of A. fulvicoma within the genus Actinidia.